Tourism marketing in East and Southeast Asia - Stylidis, Dimitrios; Kim, Seongseop; Kim, Jungkeun (Wallingford, Oxfordshire CABI, 2023)
"Despite the increased research interest in tourism in Asia, most research has focused on the key destinations the region hosts (China, Macao, Honk Kong, Thailand), neglecting others which are less well explored. As such little is known about the marketing efforts and practices along with the successes and challenges countries in the Southeast Asia sub-region have been experiencing. This book aims to address this oversight by exploring the marketing approaches, techniques and tools used by various countries in the region both collectively and individually to manage their tourism offerings and position them in the global tourism market: China, Indonesia, Japan, Korea, Macao, Mongolia, Myanmar, Vietnam.

It offers a contemporary and insightful look at the various case studies in Southeast Asia using inter-disciplinary perspectives and a range of methodological approaches and tools;It provides case studies developed by tourism researchers who are experts in their researched context countries;It focuses on several countries which are at different stage of development;It explores specific marketing strategies in Southeast Asian destinations, considering global trends and forces to understand the marketing environment.
The book will be of interest to tourism marketing researchers, practitioners, academics, undergraduate and postgraduate students who will find these insightful contemporary case studies useful in a classroom."--
Contributors
Contributors’ Biographies
Introduction
1 Implications of Culture for Tourism and Hospitality Marketing Mix in East and Southeast Asia
2 Factors Influencing Decision Making of Millennial Travellers Participating in Community-Based Rural Tourism Experiences in Southeast Asia
3 Visual Destination Images: The Case of the ASEAN Tourism Organization Official Instagram Account
4 Effectiveness of Advertisement Endorsement and Framing to Promote Korea as a Medical Tourism Destination: Cross-Cultural Approach
5 The Interaction Between Destination Image, Risk Perceptions and Travel Intention: The Case of Myanmar
6 Exploring the Destination Image of Mongolia: A Content Analysis
7 Young Indonesian Travellers’ Information Search Behaviour
8 The Perceived and Projected Image of Hiroshima: A Case Study of the Dutch Market
9 Destination Marketing Using Festivals in Macau: Relationships Between Festival Performance Quality, Experiential Quality, Visitor Satisfaction, Corporate Image and Behavioural Intention
10 New Cyber Laws: A Plausible Discussion Regarding the Potential Implications for International Tourists in the Socialist Republic of Vietnam
11 Growth of the Senior Tourism Market and Its Implications for Destination Marketers: Understanding Tourism Motivation and Preferences Through Comparison of Seniors in Korea, Mainland China and the USA
Conclusion
Index
Includes bibliographical references and index.
Keywords: Tourism -- Marketing; Strategic planning; Tourism -- Marketing -- East Asia; Tourism -- Marketing -- Southeast Asia; Hospitality industry -- Management; East Asia; Southeast Asia